Organizational Midline Study: Rupandehi, Nepal - Nagpal, Mansi; Khatri-Chhetri, Arun (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This report summarizes findings from the Organizational Midline Survey (OMS) conducted in Nepal’s Rupandehi district in July 2019. The findings point out many organizations collaborating and coordinating with farming communities in Rupandehi. Ten of these organizations, working directly with farmers groups, were interviewed during this study.